Optimizing 3-Axis CNC Structure using ANSYS - Nguyen, Trong Hai; Ngo, Van Luc; Dinh, Van Thang (Old Journal, 2019)
In this study ANSYS software will be used to optimize structure of a CNC 3-axis machine. The objective of this study is to gain the optimal structure for the machine with sufficient stiffness and minimal weight. The structure then will be redesigned by removing irrelevant material at low-stress areas. Stiffness and strength of the new structure will be analyzed to guarantee the qualified function of the structure with lowest cost of material. This study only focuses on static loads because of the working characteristic of the designed machine. The optimized structure has been manufactured and the machine has been assembled and tested under working conditions. The machine has enough stiffness and lightweight.